New developments in the management of severe skin and deep skin structure infections – focus on tedizolid - Durkin MJ; Corey GR (Dove Medical Press, 2015)
Michael J Durkin,1 G Ralph Corey2,3 1Department of Medicine, Division of Infectious Diseases, Duke University, Durham, NC, USA; 2Department of Medicine, Duke Clinical Research Institute, Durham, NC, USA; 3Duke Global Health Institute, Durham, NC, USA Abstract: Tedizolid, a novel oxazolidinone, is approved for treatment of acute bacterial skin and skin structure infections (ABSSSIs). Tedizolid offers several potential advantages over current ABSSSI treatment options. First, tedizolid has a prolonged half-life, which allows for once-daily dosing. Second, tedizolid has broad spectrum activity against Gram-positive organisms including methicillin-resistant Staphylococcus aureus, coagulase-negative staphylococci, and enterococci. Third, tedizolid, available in both intravenous and oral formulations, has high oral bioavailability, allowing for easy oral step-down therapy. Fourth, in patients who have been prescribed selective serotonin reuptake inhibitors or monoamine oxidase inhibitors, tedizolid may have fewer drug interactions than linezolid. Finally, tedizolid may have fewer or comparatively delayed onset side effects than linezolid, including thrombocytopenia and nausea. This review covers the microbiology, pharmacology, mode of action, and pharmacokinetics of tedizolid as well as patient-focused perspectives such as quality of life, patient satisfaction/acceptability, adherence, and uptake and provides expert opinion on the current use of tedizolid for ABSSSIs and potential future therapeutic applications. Keywords: cellulitis, new antibiotics, oxazolidinones, infectious diseases, MRSA